HUBUNGAN ANTARA KUALITAS TIDUR DAN KADAR HEMOGLOBIN DENGAN KELELAHAN (FATIGUE) PADA PASIEN KANKER YANG MENJALANI TERAPI KEMOTERAPI DI RS KANKER DHARMAIS - Bridemi Yanti B; Febi Ratnasari (Nusantara Hasana Journal, 2022)
Chemotherapy is one of the main therapies for cancer patients given to patients with systemic cancer and cancer with clinical or subclinical metastases. Chemotherapy therapy can cause side effects that can be detrimental to some of the patient’s physiological functions. The purpose of this study was to determine the relationship between sleep quality and hemoglobin levels with fatigue in cancer patients undergoing chemotherapy therapy at Dharmais Cancer Hospital. This study used a correlational research design with a cross sectional study approach with a sample of 110 respondents taken with simple random sampling technique. The results showed that the majority of cancer patients who underwent chemotherapy at Dharmais Hospital were in years old. 45 years (75.5%), the majority are female (72.7%), the majority have Hb in the anemia category (66.4%), the majority have poor sleep quality (52.7%), and the majority experience fatigue weight (63.6%). There is a relationship between Hb levels (p: 0.000) and sleep quality (p: 0.003) with cancer patients undergoing chemotherapy at Dharmais Hospital.